2009
DOI: 10.1159/000257494
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin-3-O-gallate Decreases Tumor Necrosis Factor-α–induced Fractalkine Expression in Endothelial Cells by Suppressing NF-ĸB

Abstract: Epigallocatechin-3-O-gallate (EGCG), the main catechin in green tea, has anti-oxidant, anti-atherosclerotic and anti-inflammatory properties. Fractalkine, a chemokine involved in inflammation and early atherosclerotic processes, acts as a chemoattractant as well as an adhesion molecule in endothelial cells activated by proinflammatory cytokines. In the present study, we investigated the effect of EGCG on fractalkine expression in TNF-α-induced human umbilical vein endothelial cells (HUVECs). EGCG decreased TNF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 30 publications
(47 reference statements)
1
23
0
Order By: Relevance
“…In our study, the concentrations of EGCG (10-50μM) are generally within the range used in most published in vitro studies [27,28,29]. Nevertheless, the relatively high concentrations of EGCG obtained in cell culture studies have been considered to far exceed the levels found in human plasma after green tea consumption.…”
Section: Discussionsupporting
confidence: 54%
“…In our study, the concentrations of EGCG (10-50μM) are generally within the range used in most published in vitro studies [27,28,29]. Nevertheless, the relatively high concentrations of EGCG obtained in cell culture studies have been considered to far exceed the levels found in human plasma after green tea consumption.…”
Section: Discussionsupporting
confidence: 54%
“…Our previous data showed that TNF-α-induced expression of fractalkine occurs mainly through the activation of the NF-κB and PI3-K pathways [28]. Recently, we reported that genistein protects against cisplatin-induced renal injury via the NF-κB signaling pathway [22].…”
Section: Discussionmentioning
confidence: 99%
“…EGCG decreased TNF-ainduced fractalkine expression by suppressing NF-jB 44 and inhibited TNF-a-induced MCP-1 production and the activation of AP-1 in vascular endothelial cells using heme oxygenase-1 (HO-1)-dependent mechanisms. 45,46 Apigenin is a flavone that is the aglycone of apiin isolated from parsley and celery.…”
Section: Discussionmentioning
confidence: 99%